2010
DOI: 10.5194/acp-10-1773-2010
|View full text |Cite
|
Sign up to set email alerts
|

Light absorption by organic carbon from wood combustion

Abstract: Abstract. Carbonaceous aerosols affect the radiative balance of the Earth by absorbing and scattering light. While black carbon (BC) is highly absorbing, some organic carbon (OC) also has significant absorption, especially at near-ultraviolet and blue wavelengths. To the extent that OC absorbs visible light, it may be a non-negligible contributor to positive direct aerosol radiative forcing. Quantification of that absorption is necessary so that radiative-transfer models can evaluate the net radiative effect o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

57
638
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 673 publications
(704 citation statements)
references
References 72 publications
57
638
9
Order By: Relevance
“…For black carbon, MAE values are in the range of 6.5-7.5 m 2 g −1 at 850 nm (Bond and Bergstrom, 2006;Massabò et al, 2016) and decrease in a linear way with the logarithm of the wavelength. For brown carbon, the reported MAE range between 2.3 and 7.0 m 2 g −1 at 350 nm (Chen and Bond, 2010;Kirchstetter et al, 2004;Massabò et al, 2016), 0.05 and 1.2 m 2 g −1 at 440 nm (Wang et al, 2016) and 0.08 and 0.72 m 2 g −1 at 550 nm (Chen and Bond, 2010). The analysis of Table 4 indicates that, at every wavelength, the MAE values in the PM 2.5 fraction are equal or higher than those for PM 10.6 .…”
Section: Spectral and Size Variability Of The Mass Absorption Efficiencymentioning
confidence: 99%
“…For black carbon, MAE values are in the range of 6.5-7.5 m 2 g −1 at 850 nm (Bond and Bergstrom, 2006;Massabò et al, 2016) and decrease in a linear way with the logarithm of the wavelength. For brown carbon, the reported MAE range between 2.3 and 7.0 m 2 g −1 at 350 nm (Chen and Bond, 2010;Kirchstetter et al, 2004;Massabò et al, 2016), 0.05 and 1.2 m 2 g −1 at 440 nm (Wang et al, 2016) and 0.08 and 0.72 m 2 g −1 at 550 nm (Chen and Bond, 2010). The analysis of Table 4 indicates that, at every wavelength, the MAE values in the PM 2.5 fraction are equal or higher than those for PM 10.6 .…”
Section: Spectral and Size Variability Of The Mass Absorption Efficiencymentioning
confidence: 99%
“…Second, we treated all the water-insoluble OC from the ice-core measurements as lightabsorbing brown carbon in the forcing estimation, which also likely results in an overestimation of OC forcing if a significant fraction of OC is non-absorbing. However, the watersoluble part, accounting for about half of OC observed in the Manora peak and northwestern India (Ram et al, 2010;Rajput et al, 2014), can also contribute to some absorption of UV and visible light (Chen and Bond, 2010;Beine et al, 2011). Thus, the absorption by water-soluble OC that was not included in the forcing estimate may compensate for the high bias to some extent.…”
Section: Radiative Forcing Induced By Carbonaceous Aerosols In Tibetamentioning
confidence: 99%
“…Little is known about aerosol properties in this spectral region, although several recent studies have suggested that particle absorption increases strongly at sub-visible wavelengths. [53][54][55] …”
Section: Atmospheric Implications and Applicationsmentioning
confidence: 99%